Rapid uniform rotation of proto-neutron stars, hot neutron stars, and neutron star merger remnants: The role of the temperature - Koliogiannis Koutmiridis, Polychronis Stylianos (HNPS Advances in Nuclear Physics, 2022)
Hot and dense nuclear matter and the equation of state is mandatory for studying proto-neutron stars and neutron star merger remnants. The applied equations of state are derived within the momentum-dependent interaction model and state-of-the-art microscopic data, to fulfill the thermodynamic laws. The matter is constructed under the assumptions of finite temperature and beta-equilibrium state, and finite entropy per baryon and varying values of proton fraction. Afterwards, we study the effects of finite temperature and rotation at the mass-shedding limit on the neutron stars properties, including the mass and radius, the moment of inertia, the frequency, the Kerr parameter, the central baryon density, etc. The interplay between the temperature and rotation for proto-neutron stars and neutron star merger remnants may shed light in the construction of the equation of state of nuclear matter and apply robust constraints.